Extreme precipitation events and erosion in the Santa Maria river hydrographic basin (RS) - Petsch, Carina (2023)
The extreme precipitation events (EEP) are presented as triggers of several natural disasters, being able to trigger, for example, erosion processes with the disaggregation and transport of sedimentary material. Studies for the Santa Maria river basin (BHRSM), located in the southwest of Rio Grande do Sul, indicate that linear erosion features (FEL) occur mainly in friable rocks and portions with high erosivity of precipitation. The objective of this study is to identify and characterize the EEP of the BHRSM and evaluate its relationship with erosion processes. The EEP were obtained from the application of the 99th percentile with data from seven meteorological stations (EM), between 1986-2020. The spatialization and crossing of the data were performed in QGIS. BHRSM had a total of 695 EEP. It is verified that annually the years with more EEP are those with positive ONI (Oceanic Niño Index). Seasonally, spring and autumn are the seasons with more EEP, which is linked to Mesoscale Convective Complexes. The months with the most extreme events coincide with the planting and harvesting of soybeans, due to land management, the soil can be exposed and consequently trigger erosion processes. Spatially, it was observed that the predominance of FEL occurs in the EM Ponte Toropi II area of influence, which concentrates 50% of the extreme events of the BHRSM. This study pointed out that there may be a development of FEL due to the EEP - in addition to the context of poorly consolidated sandy substrate that already configure a scenario of environmental fragility for the BHRSM.